Structural and magnetic properties of nanocrystalline Bi1-xLaxFeO3 (0.0 ≤ x ≤ 0.4) synthesized by a mechanochemical route - Cristóbal, Adrián Alberto; Ramos, Cinthia Paula; Conconi, María Susana; Bercoff, Paula Gabriela; Botta, Pablo Martín (2024)
Artículo finalmente publicado en: Cristóbal, A. A., Ramos, C. P., Conconi, M. S., Bercoff, P. G. y Botta, P. M. (2017). Structural and magnetic properties of nanocrystalline Bi1-xLaxFeO3 (0.0 ≤ x ≤ 0.4) synthesized by a mechanochemical route. Materials Research Bulletin, 95. https://doi.org/10.1016/j.materresbull.2017.07.035